Symmetric Merge and Local Instability: Evidence from Split Topics. (13th March 2015) - Ott, Dennis
Abstract: In this paper, I argue against the standard analysis of so‐called split topics in German as discontinuous noun phrases (van Riemsdijk 1989). Building in part on Fanselow 1988, I show that the construction rather involves two morphosyntactically autonomous nominal constituents that are predicatively related in underlying form. This predication is syntactically unstable, however. Merge of two XPs within a single argument or adjunct position yields a symmetric structure for which no label ("head") can be detected by Minimal Search ("for any syntactic object α, β , α is the head if α is a lexical item"; see Chomsky 2008). Therefore, one of the two noun phrases must move at the phase level in order to render the structure asymmetric; in case the stranded noun phrase is elliptical, the impression of a discontinuous constituent arises. By providing a principled explanation for split topicalization in these terms, the analysis furnishes evidence for an architecture in which Merge applies freely ( pace recent claims to the contrary, e.g., in Kayne 2010), and as an asymmetrizing device when applying internally (as movement), in the spirit of Moro 2000 and Chomsky 2013.